2008
DOI: 10.1084/jem.20072528
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of TNF receptor superfamily 25 (TNFRSF25) in the development of allergic lung inflammation

Abstract: We identify the tumor necrosis factor receptor superfamily 25 (TNFRSF25)/TNFSF15 pair as critical trigger for allergic lung infl ammation, which is a cardinal feature of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
206
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(227 citation statements)
references
References 41 publications
12
206
1
5
Order By: Relevance
“…Consistent with these findings transgenic mice that constitutively express TL1A have increased levels of IL-13 and IL-17 but not IFN-g under steady-state conditions [15,16]. However, other studies have shown that addition of TL1A or agonist anti-DR3 mAb enhances the production of both IL-4 and IFN-g during in vitro activation of naïve CD4 1 T cells [5,14]. To decipher the role of DR3 in host immunity to infection, we have examined the immune response against Salmonella enterica serovar Typhimurium in DR3-deficient mice.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Consistent with these findings transgenic mice that constitutively express TL1A have increased levels of IL-13 and IL-17 but not IFN-g under steady-state conditions [15,16]. However, other studies have shown that addition of TL1A or agonist anti-DR3 mAb enhances the production of both IL-4 and IFN-g during in vitro activation of naïve CD4 1 T cells [5,14]. To decipher the role of DR3 in host immunity to infection, we have examined the immune response against Salmonella enterica serovar Typhimurium in DR3-deficient mice.…”
mentioning
confidence: 65%
“…Furthermore, reports describing a role for DR3 in Th1-cell responses are conflicting. In vitro, CD4 1 T cells that cannot signal via DR3 are defective in the secretion of a number of cytokines including IL-2, IL-4, IL-5, IL-13, IL-10, IL-17, but not IFN-g [5,14]. Furthermore, addition of TL1A enhanced the proliferation of in vitro generated Th17 cells upon re-stimulation, but had no effect on the proliferation of Th1 cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…TNFR superfamily (TNFRSF)25, a member of the TNFR superfamily, is a type I transmembrane protein that has a cytoplasmic death domain with homology to TNFR1 (2-7). TNFRSF25 is expressed primarily by T lymphocytes, including CD4 + , CD8 + , and NKT cells (3)(4)(5)(6)(7)(8) and is efficiently upregulated after TCR stimulation. The natural ligand for TNFRSF25 was identified as TNF superfamily member 15 (TL1A) (9), which is a trimeric type II transmembrane protein that can be cleaved by metalloproteases and released as a functional and soluble trimer (10).…”
Section: S Everal Members Of the Tnf Superfamily Expressed By T Cellsmentioning
confidence: 99%
“…Cyclosporin A was purchased from Calbiochem/ EMD Millipore. Armenian hamster hybridoma producing Ab to mTNFRSF25 (agonist 4C12) was maintained as described previously (8). 4C12 (anti-TNFRSF25 agonist) and L4G6 (anti-mTL1A blocking mAb) was produced in hollow fiber bioreactors (Fibercell Systems) and purified from serumfree supernatants on a protein G column using PBS for elution.…”
Section: Flow Cytometry Abs and Reagentsmentioning
confidence: 99%
“…TL1A also promotes Treg proliferation and attenuates Treg-mediated suppression of non-regulatory CD4 1 T cells [9]. In addition, TL1A has been shown to costimulate invariant NKT cells [10] and may have a role in enhancing NK cell-mediated tumor cell killing [11]. …”
Section: Introductionmentioning
confidence: 99%